Expérimentations concernant l’adaptabilité de certaines espèces de poissons dulçaquicoles au milieu saumâtre - Ioniță, Reveica (Cercetări Marine - Recherches Marines, 2026)
Preliminary results of the laboratory experiments on carp (Cyprinus carpio carpio) spawn adaptability to about 5‰ to and 10‰ salinities and on zander (Stizostedion lucioperca) spawn adaptability to the Black Sea salinity (18‰) are presented. The carp spawn achieved a growth increase of about 50‰ greater for 5‰ salinity as related to 10‰ salinity. The zander spawn behaved normally at salinities up to 18‰.